Dynamic Model of a Rotating Flexible Arm-Flexible Root Mechanism Driven by a Shaft Flexible in Torsion - S.Z. Ismail; A.A. Al-Qaisia; B.O. Al-Bedoor (Shock and Vibration)
This paper presents a dynamic model of a rotating flexible beam carrying a payload at its tip. The model accounts for the driving shaft and the arm root flexibilities. The finite element method and the Lagrangian dynamics are used in deriving the equations of motion with the small deformation theory assumptions and the Euler-Bernoulli beam theory. The obtained model is a nonlinear-coupled system of differential equations. The model is simulated for different combinations of shaft and root flexibilities and arm properties. The simulation results showed that the root flexibility is an important factor that should be considered in association with the arm and shaft flexibilities, as its dynamics influence the motor motion. Moreover, the effect of system non-linearity on the dynamic behavior is investigated by simulating the equivalent linearized system and it was found to be an important factor that should be considered, particularly when designing a control strategy for practical implementation.